A Brief History of the Sales Environment - Micah Strader; Allen Wysocki (EDIS)
This document is SN001, one of a series of the Food and Resource Economics Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date January 2002. Reviewed October 2008.